Not a Gift: Phenomenological Research of Everyday Experience - Latinytė, Rūta (Tautosakos darbai, 2019)
By using approaches of phenomenological anthropology and research of everyday experience, the author of the article introduces a possibility to study practices of gift giving and receiving, occurring in modern social life. Special attention is paid to a peculiar case of the gift giving – when a gift is not given, and the act of gift giving does not take place.Every instance of gift giving or losing presents a unique moment in the life of an individual experiencing the world. The author analyzes descriptions of experience and qualitative unstructured interviews with commentaries, conducted especially for the purposes of this study, as well as her own experiences, which is typical for the method of phenomenological research. Various experiences of gift giving that did not take place are presented in the article. The first one can be defined as refusing of the gift – when an individual bringing a whiskey bottle in gratitude for his boss’s help was kicked out from the latter’s office. The second case comprises instances of memory loss from the perspective of the gift giver and the receivers. Numerous interviewees were not able to remember any gifts received from their spouses, although the gift exchange in the family was practiced during holidays every year. However, the gifts that some close persons had forgotten to give, or that were repeatedly given, present quite another matter from the point of view of the giver that still remembers them. The third case comprises the gift that was meant yet not given – a work of art dedicated to a well-known musician, but staying in the interviewee’s home. The fourth case centers on a dramatic story of a woman who abnormally accumulated stuff in her house during her whole life, but has not once given anything to her family. After her tragical demise in a fire, her family members found various things at her home and reshaped their personal attitude towards her, making the author to reconsider her attitude as well.The analysis reveals ways in which the ungiven gifts both reflect and affect the interpersonal relationships, and possible meaning and place of these experiences in people’s memory. The impossibility of the gift giving is recognized in every story as a state of uneasiness, as a certain lapse in time. It indicates a shift in perception of the interpersonal relationship and highlights the necessity of re-evaluation of the relationship that was supposed to be established by the ungiven gift.The ungiven gift puts people off their stride, depriving them of the possibility of time for a while: it makes them understand that the Other is actually different from that Other, who the subject imagined existing in their mutual relationship. The rational consciousness feels lost, and until it finds another “I” in relation to the Other, the only possible relationship is the one between “I” and “Myself”, which is separated from the world, time, and existence. However, the individual can move from the state of passive helplessness and adopt an active role in the mastership game. The concept of the mastership game presupposes an objective to influence the world that does not belong to the individual like the Other, but can be appropriated as a masterfully created game instead, subsumed by way of recognizing the meaning.The mastership game is a creative movement that presupposes searching for a new meaningful form. Thus, the gift is also a creative act: while being unable to influence the Other, the subject becomes engaged in a game and replaces the intersubjective relationship with a connection between the subject and the object (gift). Therefore, two mutually immanent subjects are related by the gift that makes their interrelationship meaningful; or, likewise, become separated, when the gift is not given.
Keywords: gift; exchange; human relationship; research of everyday experience; phenomenological anthropology